2016
DOI: 10.1111/ases.12349
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating distribution of the left branch of the middle colic artery and the left colic artery by CT angiography and colonography to classify blood supply to the splenic flexure

Abstract: Introduction: CT angiography has gained widespread acceptance for preoperative

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
52
1
8

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(63 citation statements)
references
References 19 publications
2
52
1
8
Order By: Relevance
“…The origin of the artery was in the superior mesenteric artery in 47 cases (67.1%; 32.9% of the total), in the inferior mesenteric artery in 21 cases (30%; 14.9% of the total), and in the celiac artery in two cases (2.9%; 1.4% of the total). As previous studies report that it exists in 4-8% of cases in the USA and Europe, and in 33-49% of cases in Japan [1,4,7,15,20,21,28,30], its frequency of occurrence in the present study (48.9%) is high. Moreover, although there are reports of an accessory middle colic artery that arises in the inferior mesenteric artery, it occurs infrequently, appearing in 5-9% of cases (30% in the present study) [20,30].…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…The origin of the artery was in the superior mesenteric artery in 47 cases (67.1%; 32.9% of the total), in the inferior mesenteric artery in 21 cases (30%; 14.9% of the total), and in the celiac artery in two cases (2.9%; 1.4% of the total). As previous studies report that it exists in 4-8% of cases in the USA and Europe, and in 33-49% of cases in Japan [1,4,7,15,20,21,28,30], its frequency of occurrence in the present study (48.9%) is high. Moreover, although there are reports of an accessory middle colic artery that arises in the inferior mesenteric artery, it occurs infrequently, appearing in 5-9% of cases (30% in the present study) [20,30].…”
Section: Discussionsupporting
confidence: 54%
“…The 7% of cases in the present study in which the ascending artery divided and became the left colic artery and accessory middle colic artery would be included among such cases. In a study of 191 cases in which the blood supply to the splenic flexure was evaluated, there was only one case in which the arc of Riolan connected these two marginal arteries [4]. We believe it is possible that part of the arc of Riolan mentioned in that study was the same as the vessel described in the present study that connects the left colic artery and accessory middle colic artery.…”
Section: Discussionmentioning
confidence: 43%
“…Because the image of 2D and 3D CTA can be acquired non-invasively and preoperatively, it is useful for preoperative simulation. Recently, Fukuoka et al evaluated the AMCA using 3D CTA and reported that the AMCA was present in only 6.6% of cases [4]. Recognizing the AMCA by using only 3D CTA in the case of a tiny AMCA or an AMCA originating from the SMA flow is sometimes difficult.…”
Section: Discussionmentioning
confidence: 99%
“…The MCA was defined as the branch of the SMA towards the right side, which ran to supply the transverse colon . Although the MCA typically bifurcated into right and left branches, these branches sometimes originated independently from the SMA.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation